T-cell recognition of a cross-reactive antigen(s) in erythrocyte stages of Plasmodium falciparum and Plasmodium yoelii: inhibition of parasitemia by this antigen(s). - Lucas, B (1993)
In the current study, we investigated the presence of a cross-reactive antigen(s) in the erythrocyte stage from Plasmodium yoelii (265 BY strain) and Plasmodium falciparum through recognition by T cells primed in vivo with antigens from each of these parasites. BALB/c mice are naturally resistant to P. falciparum but are susceptible to P. yoelii infection. Mice that had recovered from P. yoelii primary infection became resistant to a second infection. A higher in vitro proliferative response to a soluble blood stage preparation of P. falciparum was observed in splenic cells from immune animals than in those from mice with a patent P. yoelii infection. The antigen-induced proliferative response was enhanced when animals were exposed to a secondary infection. Animals exposed to a challenge infection were treated with anti-CD4 or anti-CD8 monoclonal antibodies to deplete the corresponding subset of T cells. There was a marked diminution in P. falciparum antigen-induced proliferative response in the total splenic cell populations from CD8-depleted but not from CD4-depleted mice. In CD8-depleted and nondepleted animals, the antigen-induced proliferation in the total cell populations was markedly lower than in the T-cell-rich populations, indicating inhibitory activities of B cells and/or macrophages. There was no such difference in the stimulation between total and T-enriched cell populations from CD4-depleted animals. Flow cytometry analysis demonstrated the presence of an almost equal percentage of CD8+ (59.6%) and CD4+ (64%) T cells in the spleen preparations following in vivo depletion of CD4- and CD8-bearing T cells, respectively. When cultured with P. yoelii blood stage antigen, splenocytes from animals immunized with P. falciparum antigen displayed a significant proliferative response which was markedly diminished by treatment with anti-Thy-1.2 antibody plus complement. Animals immunized with P. falciparum antigen and then challenged with P. yoelii blood stage parasites displayed about a 50% lower level of parasitemia. These results demonstrated the existence of a cross-reactive antigen(s) between a murine and a human Plasmodium species, as determined from both in vivo and in vitro biological assays, and indicated the reactivity of mainly CD8+ T cells with this antigen.